The relationship between vitamin D status and depression in a tactical athlete population - Kelly A. Schaad; Asma S. Bukhari; Daniel I. Brooks; Justin D. Kocher; Nicholas D. Barringer (Journal of the International Society of Sports Nutrition, 2019)
Background Stressors inherent to the military, such as combat exposure, separation from family, and strenuous training, collectively contribute to compromised psychological resilience and greatly impact military performance. Methods This retrospective review of records was conducted to determine whether vitamin D status was associated with diagnoses of depression and if diagnoses differed by geographic location. Results Depression (defined using diagnostic codes) was more prevalent in individuals who were diagnosed with vitamin D deficiency (20.4%) than in individuals who were not (4.2%). After adjustment, vitamin D deficient diagnoses remained significantly associated with depression diagnoses (OR = 1.22; 95% CI, 1.11–1.33, p < 0.001). Furthermore, vitamin D deficient diagnoses were strongly associated with geographic latitude (r 2  = 0.92, p = 0.002). Conclusion These results suggest that service members stationed at installations located at northerly latitudes may be at increased risk for vitamin D deficiency. Furthermore, vitamin D deficient service members may be at higher risk for diagnosis of depression. As a number of military service members avoid reporting symptoms or seeking treatment, vitamin D status may be a useful screening tool to identify service members at risk for depression.